Lean and Hungry or Fat and Content? Entrepreneurs' Wealth and Start-Up Performance - Hvide, Hans K.; Møen, Jarle (Management Science, 2010)
If entrepreneurs are liquidity constrained and not able to borrow to operate on an efficient scale, economic theory predicts that entrepreneurs with more personal wealth should do better than those with less wealth. We test this hypothesis using a novel data set covering a large panel of start-ups from Norway. Consistent with liquidity constraints, we find a positive relation between founder prior wealth and start-up size. The relationship between prior wealth and start-up performance, as measured by profitability on assets, increases in the first three wealth quartiles. In the top wealth quartile, however, profitability drops sharply in wealth. Our findings are consistent with a luxury good interpretation of entrepreneurship and that higher wealth may induce a less alert or a less dedicated management. We conclude that an abundance of resources might do more harm than good for start-ups.